Analisis Dimensi Propeler Untuk Kebutuhan Desain Konseptual Pesawat Piston - Rosalie, Rhea Anggun; Alimin, Edy Karyadi; Arifin, Mufti (Jurnal Teknologi Kedirgantaraan, 2022)
This research conducted a comparative analysis of propeller dimensions for the conceptual design of a piston aircraft. The method used is statistical linear regression by comparing some variables related to propellers from 27 piston aircraft data. Based on comparison results obtained 6 strong relationships, namely aircraft speed and engine power, aircraft weight and engine power, aircraft weight and propeller weight, aircraft weight and the number of propellers blades, engine power and propeller weight, and propeller weight and the number of propellers blades so that it can be used for conceptual design reference. The propeller diameter and engine speed variables do not have a strong relationship in regression but form a cluster so that it can be used as a conceptual design reference. The conceptual design simulation with an aircraft weight of 3500 lb produces a propeller with a diameter of 80 inches, the engine power of 325.51 hp, propeller weight of 86.13 pounds, engine speed of 2500 rpm, and 3 blade propellers with a thrust of 1340.05 lbf.